Efektifitas Mediasi Dalam Proses Penyelesaian Sengketa Perdata di Pengadilan Negeri Banda Aceh - Cut Nyak Tihajar; Rahmat Saputra (JURNAL HUKUM PELITA, 2025)
Settlement of civil cases through litigation is expected to be the best solution for the community to obtain legal certainty, but in practice it is not the case, because the settlement of civil cases in court can be protracted and require a lot of money. For this reason, mediation is needed as regulated in Article 130 HIR and Article 154 RBG which states that the judge is required to reconcile the disputing parties first before the trial process. The purpose of this study is to understand and analyze the effectiveness of the implementation of mediation at the Banda Aceh District Court as well as the obstacles and efforts in implementing mediation at the Banda Aceh District Court. The method used in the discussion is an empirical legal research method using a qualitative approach. The results of this study indicate that the effectiveness of mediation at the Banda Aceh District Court is still very low, only reaching 10% from 2020 to 2024. Obstacles in the implementation of mediation include the absence of the parties, the assumption that mediation is just a formality, and the passive role of attorneys in encouraging peaceful resolution. In addition, the lack of public understanding of the function of mediation is also an obstacle. Efforts that can be made include increasing socialization and legal education, utilizing technology for online mediation, training mediators and advocates, and providing sanctions or incentives for parties that hinder or encourage the success of mediation